Heart failure with reduced ejection fraction developed from valvular surgery: Risk factors and therapeutic effects of sacubitril valsartan - Chen Yuqian; Hu Qinghua; Luo Fanyan; Huang Lingjin; Chen Xuliang; Zhang Chengliang (International Journal of Cardiology: Heart & Vasculature)
Objective: To investigate the risk factors for heart failure developed from cardiac valvular surgery and the efficacy of sacubitril valsartan (ARNI). Methods: Clinical data from patients with left ventricular ejection fraction (LVEF) ≥ 50 % who consecutively underwent cardiac valvular (mitral/aortic valve) surgery in 2021 were collected. Pre − and intra − operative variables were analyzed to explore risk factors for HFrEF (LVEF ≤ 40 %). Post − operative HFrEF patients were split into ARNI − treated (n = 15) and non-ARNI − treated (n = 15) groups. Follow − up echocardiography data were compared to assess ARNI’s efficacy. Results: Among 420 patients undergoing valve surgery (117 aortic, 133 mitral, 170 double-valve), 34 (8.1 %) developed HFrEF, showing significantly higher in-hospital mortality than non-HFrEF patients (8.82 % vs 0.52 %). Multivariate analysis identified preoperative left ventricular diameter as an independent HFrEF risk factor. During follow-up, 70 % of HFrEF patients achieved LVEF > 50 % within 6 months, Repeated-measures F test demonstrated significantly greater LVEF improvement (P = 0.036) and LVEDD reduction (P = 0.014) in the ARNI group versus non-ARNI group. Conclusions: About 8 % of patients with LVEF ≥ 50 % developed HFrEF after cardiac valvular surgery, and large left ventricular diameter was an independent risk factor. Sacubitril valsartan is very effective in improving left ventricular remodeling and LVEF in such cohort.